2019
DOI: 10.1186/s13048-019-0543-z
|View full text |Cite
|
Sign up to set email alerts
|

Pathological features, clinical presentations and prognostic factors of ovarian large cell neuroendocrine carcinoma: a case report and review of published literature

Abstract: Background There is no consensus on the optimal chemotherapy regimen and the prognostic factors for ovarian large cell neuroendocrine carcinoma (LCNEC), a rare type of tumor. The objective of the present study is to present the case of a recent encounter of pure ovarian LCNEC and perform a brief review to summarize the clinicopathological features and prognostic factors of 57 cases of LCNEC patients that have been previously reported. Method: case presentation Eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 62 publications
0
42
0
Order By: Relevance
“…The adjuvant chemotherapy regimens for patients with neuroendocrine carcinoma of the ovary are not reported in the SEER database. Yang et al reviewed sporadic case reports and found that 86% of 58 cases received adjuvant chemotherapy, and platinum-based regimens accounted for the majority of the cases, but this small group analysis did not confirm survival benefits from chemotherapy 21. The paucity of data still suggests that etoposide/platinum chemotherapy may be of benefit to patients.…”
Section: Discussionmentioning
confidence: 99%
“…The adjuvant chemotherapy regimens for patients with neuroendocrine carcinoma of the ovary are not reported in the SEER database. Yang et al reviewed sporadic case reports and found that 86% of 58 cases received adjuvant chemotherapy, and platinum-based regimens accounted for the majority of the cases, but this small group analysis did not confirm survival benefits from chemotherapy 21. The paucity of data still suggests that etoposide/platinum chemotherapy may be of benefit to patients.…”
Section: Discussionmentioning
confidence: 99%
“…50% recurred within 6 months of chemotherapy, which suggested that these tumors might respond poorly to chemotherapy. Yang et al reviewed sporadic case reports, and their study did not con rm survival bene ts from chemotherapy [24]. Two patients who received EP have been followed up for 24 and 27 months, without disease.…”
Section: Discussionmentioning
confidence: 98%
“…50% recurred in 6 months of chemotherapy, which suggested that these tumors might respond poorly to the chemotherapy. Yang et al reviewed sporadic case reports, and their study failed to con rm survival bene ts from chemotherapy [24]. Two cases who received EP have been followed up for 24 and 27 months, without any diseases.…”
Section: Discussionmentioning
confidence: 99%